2018
DOI: 10.1089/fpd.2017.2332
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Genetics and Functionality of Plasmids in Incompatibility Group I1-PositiveSalmonella enterica

Abstract: Salmonella is a predominant foodborne pathogen in the United States and other countries. Mobile genetic elements such as plasmids allow Salmonella to adapt to external stress factors such as nutrient deprivation and host factors. Incompatibility group I1 (IncI1) plasmid-carrying Salmonella enterica strains were examined to determine the presence of plasmid-associated genes and their influence on phenotypic characteristics. The objective of this study was to understand the genetic determinants on IncI1 plasmids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(31 citation statements)
references
References 45 publications
4
27
0
Order By: Relevance
“…Resistance to ceftiofur in the S. Typhimurium isolate was likely mediated by bla CMY , which has been previously associated with the IncI1 plasmid which was also identified via whole genome sequencing in this isolate (58). In theory it is possible that transfer of these AMR genes may have occurred between our isolates in vivo, however, further investigation would be necessary to definitively prove that the bla CMY gene was indeed located on this plasmid and determine if conjugative transfer genes such as tra or pil were present on same plasmid which would make the possibility of transfer more likely (58). Of the two resistance genotypes utilized for differentiation in this study, it is much more likely that exchange of plasmidassociated genes such as bla CMY could have occurred rather than exchange of genes believed to be chromosomally-located.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Resistance to ceftiofur in the S. Typhimurium isolate was likely mediated by bla CMY , which has been previously associated with the IncI1 plasmid which was also identified via whole genome sequencing in this isolate (58). In theory it is possible that transfer of these AMR genes may have occurred between our isolates in vivo, however, further investigation would be necessary to definitively prove that the bla CMY gene was indeed located on this plasmid and determine if conjugative transfer genes such as tra or pil were present on same plasmid which would make the possibility of transfer more likely (58). Of the two resistance genotypes utilized for differentiation in this study, it is much more likely that exchange of plasmidassociated genes such as bla CMY could have occurred rather than exchange of genes believed to be chromosomally-located.…”
Section: Discussionmentioning
confidence: 69%
“…Further investigation of the genotypic antimicrobial resistance genes present in the isolates suggests that the resistance to gentamicin in the S. 4, [5],12:i:-isolate was likely mediated through the strA/strB genes which have been shown to be frequently inserted into the chromosome in S. 4, [5],12:i:-ASSuT resistant isolates (48,49). Resistance to ceftiofur in the S. Typhimurium isolate was likely mediated by bla CMY , which has been previously associated with the IncI1 plasmid which was also identified via whole genome sequencing in this isolate (58). In theory it is possible that transfer of these AMR genes may have occurred between our isolates in vivo, however, further investigation would be necessary to definitively prove that the bla CMY gene was indeed located on this plasmid and determine if conjugative transfer genes such as tra or pil were present on same plasmid which would make the possibility of transfer more likely (58).…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with the results of this study, Coplin et al (1989) reported that the plasmid was able to encode an antagonistic protein [ 31 ]. In addition, it has been reported that with the help of the plasmid, bacteria were able to obtain new phenotypes such as antibiotic resistance, pathogenicity and metabolic capacity [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The three most frequent ORIs identified in Salmonella isolates, excluding the 851 putative ORIs, were the transferable IncFII (n isolate = 533), IncFIB (n isolate = 371), and IncI (n isolate = 142) ( Table 1). All three Inc group plasmids have been shown to carry virulence-associated and AMR genes within Enterobacteriaceae [14,[27][28][29][30]. The majority of the IncFII and IncFIB ORIs were identified from S. Enteritidis and S. Typhimurium (Table 1) (at 33% and 28% for IncFII and at 47% and 39% for IncFIB, respectively).…”
Section: Construction Of a Bioinformatics Pipeline For Plasmid Identimentioning
confidence: 99%